The Association between Changes in External Environment Caused by Migration and Inappropriate Antibiotic Use Behaviors among Chinese University Students: A Cross-Sectional Study - Jingjing Lu; Xiaomin Wang; Leesa Lin; Ziming Xuan; Yanhong Jessika Hu; Xudong Zhou (MDPI AG, 2019)
Objectives: This study aims to explore how changes in external factors caused by migration impact antibiotic use behaviors among Chinese university students in comparison to their peers from host areas and origin areas. Migration status was determined by host universities and origin areas, which were broadly defined as eastern vs. western regions in China. Methods: This study analyzed secondary data from a cross-sectional study conducted in China about the antibiotic use behaviors of university students in 2015. Students were divided into four groups: eastern local students (E-Es), western local students (W-Ws), eastern−western migrant students (E-Ws), and western−eastern migrant students (W-Es). Results: After controlling for gender, grade, major, hometown (rural or urban), and parents’ education, E-Ws reported a significantly higher odds of asking for antibiotics (OR = 2.13; 95% CI = 1.54−3.03; p < 0.001) and taking antibiotics prophylactically (OR = 1.85; 95% CI = 1.32−2.56; p < 0.001) compared with E-Es; W-Es reported a significantly lower odds of asking for antibiotics (OR = 0.56; 95% CI = 0.37−0.83; p < 0.01) and taking antibiotics prophylactically (OR = 0.57; 95% CI = 0.41−0.81; p < 0.01) compared with W-Ws. Discussion: Regional differences likely interacted with students’ migration status in forming different antibiotic use behaviors. Factors including financial incentives and loose regulations of antibiotic over-prescription by health providers and peer influence may contribute to worsened antibiotic use behaviors among E-Ws.